An Unusual Etruscan Gold Dental Appliance from Poggio Gaiella, Italy: Fourth in a Series - Marshall Joseph Becker (Dental Anthropology Association, 1996)
Among the 20 known ancient dental prostheses from Etruscan archaeological contexts in an unusual example that was recovered for Poggio Gaiella, Italy. The form and construction technique used in making the Poggio Gaiella piece suggests that it was used as a restraining band to hold loose teeth in place within a maxilla. The possibility that these appliances provide evidence for early cases of leprosy rather than tooth evulsion is discussed.